Student Perceptions On Reading English Economic Texts - Adys, Himaya Praptani (Adjektiva: Educational Languages and Literature Studies, 2025)
This study investigates the perceptions of Development Economics students regarding their experiences reading English economic texts. The research examined attitudes, challenges, and strategies of 109 first-semester students (31 males, 78 females) enrolled in an English for Economics course. Using a mixed-methods approach, data was collected through a comprehensive perception survey and analyzed using both quantitative and qualitative methods. Results reveal that students perceive economic texts as highly challenging primarily due to specialized terminology, complex sentence structures, and the dual difficulty of mastering both language and content simultaneously. While students acknowledge the importance of English economic texts for their professional development, they report moderate confidence in their reading abilities. The study provides practical implications for English for Specific Purposes (ESP) instruction in economics programs and suggests approaches to enhance students' engagement with English economic texts.